2021
DOI: 10.1055/s-0041-1732781
|View full text |Cite
|
Sign up to set email alerts
|

Presence of Gingival Recession or Noncarious Cervical Lesions on Teeth under Occlusal Trauma: A Systematic Review

Abstract: The goal of this research was to carry out a systematic review to verify the possible influence of occlusal factors on the occurrence of gingival recession and noncarious cervical lesions. To answer the specific research question—whether gingival recession or noncarious cervical lesions on teeth are present under occlusal trauma—a bibliographic search was conducted at MEDLINE/PubMed, Web of Science, and Gray Literature databases focusing on articles published, following strict inclusion criteria based on rando… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 40 publications
1
3
0
Order By: Relevance
“…The explanation could be given by the presence of premature contacts and occlusal interferences specific to teeth with primary or slightly modified occlusal morphology. The same explanation is given by Troia in 2021 [31] and Chandrathara in 2020 [32].…”
Section: Discussionsupporting
confidence: 61%
“…The explanation could be given by the presence of premature contacts and occlusal interferences specific to teeth with primary or slightly modified occlusal morphology. The same explanation is given by Troia in 2021 [31] and Chandrathara in 2020 [32].…”
Section: Discussionsupporting
confidence: 61%
“…GRs increase the incidence of root caries and hypersensitivity, which are related to the onset of non-carious cervical lesions (NCCL) [25]. In addition, teeth being subjected to exacerbated forces (traumatic occlusion) seems to be associated with the occurrence of NCCL.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, teeth being subjected to exacerbated forces (traumatic occlusion) seems to be associated with the occurrence of NCCL. A systematic study [25] concluded that it was not possible to draw conclusions regarding the relationship between GR and the presence of occlusal trauma. Therefore, patients commonly seek treatment for tooth hypersensitivity or esthetic concerns [26].…”
Section: Introductionmentioning
confidence: 99%
“…Abfraction lesions are understood as having a multifactorial etiology, and represent an irreversible pathologic damage to the tooth's hard tissue [2,8]. They are localized along dental crowns' labial or buccal cervical zone, especially in premolars and the cervical area of incisors, canines, and molars [9][10][11]. According to El-Marakby et al [12], abfraction lesions are frequent in the population over 40 years of age.…”
Section: Introductionmentioning
confidence: 99%